The Effectiveness of the Indonesia Smart Program (PIP) on the Participation of High School Students in Central Java - Haris Mendra; Nasri Bachtiar (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The 2017 Susenas data revealed that the high school participation rate in Central Java was only 18.74%, leaving 81.26% of high school-aged children without access to secondary education. The Indonesia Smart Program (PIP) aims to support the education of children from low-income families; however, only 15.09% of students benefited from the program. This study examines the effectiveness of PIP on high school participation in Central Java using logistic regression analysis on 2017 Susenas data, with a sample size of 11,424 individuals. The results indicate that PIP successfully increased school participation, although other social assistance programs had a negative impact. Urban students and female students were more likely to participate in education compared to rural students and male students. These findings are crucial for formulating more effective education policies in Central Java.